In vitro SPF and photostability assays of emulsion containing nanoparticles with vegetable extracts rich in flavonoids - Cefali, Letícia Caramori (2019)
The aim of study was to determine the in vitro sun protection factor (SPF) and the photostability profile of a topical formulation composed of nanoparticles loaded with vegetable extracts and to assess its physicochemical properties. Chitosan/tripolyphosphate (TPP) nanoparticles loaded with flavonoids-enriched vegetable extracts (Ginkgo biloba L., Dimorphandra mollis Benth, Ruta graveolens, and Vitis vinifera L.) were produced and characterized for their morphology, mean particle size, zeta potential, and encapsulation efficiency. A final topical formulation was obtained by dispersing chitosan/TPP nanoparticles in an o/w emulsion. Results showed that nanoparticles dispersion exhibited yellowish color, spherical shape, and uniform appearance. Extract-loaded chitosan/TPP nanoparticles showed a mean particle size of 557.11±3.1 nm, polydispersity index of 0.39±0.27, zeta potential of +11.54±2.1 mV, and encapsulation efficiency of 75.89% of rutin. The recorded texture parameters confirm that the developed formulation is appropriate for skin application. The SPF obtained was 2.3±0.4, with a critical wavelength of 387.0 nm and 0.69 UVA/UVB ratio. The developed formulation exhibited photostability, allowing the release of flavonoids from nanoparticles while retaining rutin into the skin in a higher extension.